Estudio de vivienda sostenible en la comunidad de Rumicruz Chimborazo - Noriega Cadena, Israel Fernando (2024)
The present investigation covers the study of the community of Rumicruz in the province of Chimborazo. This territory is located at 3215 meters above sea level to 3500 meters above sea level, considered a moorland site that, through previous investigations, has been determined to be a site with a cultural wealth that has been forgotten. For reasons of community abandonment due to migration and lack of opportunities, an impact has been seen in cultural loss as well as in the abandonment of vernacular construction techniques that provided greater thermal comfort compared to current techniques, which is why through The bibliographic research, the analysis of references at a global, continental and national level, the diagnosis of the study place, a proposal for sustainable housing is proposed for the community of Rumicruz taking into account the considerations specific to the place as well as the strategies studied in the references to provide good thermal comfort inside the home, which was analyzed using the Ecotect software to ensure the result of the research. The objective of this research is to generate a guideline so that future constructions of the place take into account these considerations at the material level of the home as well as the cultural identity of the historical context of the place studied, improving the quality of life of the housing users and the Rumicruz community.